Bacteriocins as Potential Anticancer Agents - Kaur, Sumanpreet; Kaur, Sukhraj (Frontiers in Pharmacology, 2015)
Cancer remains one of the leading causes of deaths worldwide, despite advances in its treatment and detection. The conventional chemotherapeutic agents used for the treatment of cancer have nonspecific toxicity towards normal body cells that cause various side effects. Secondly, cancer cells are known to develop chemotherapy resistance in due course of treatment. Thus, the demand for novel anti-cancer agents is increasing day by day. Some of the experimental studies have reported the therapeutic potential of bacteriocins against various types of cancer cell lines. Bacteriocins are ribosomally-synthesized cationic peptides secreted by almost all groups of bacteria. Some bacteriocins have shown selective cytotoxicity towards cancer cells as compared to normal cells. This makes them promising candidates for further investigation and clinical trials. In this review article, we present the overview of the various cancer cell-specific cytotoxic bacteriocins, their mode of action and efficacies.